Lacunary statistical convergence of order ? in difference sequences of fuzzy numbers - Altinok, Hifsi; Yagdiran, Damla (Ios Press, 2016)
In this paper, we define the spaces N-theta(beta)(p, F, Delta(m)), S-theta(beta)(F, Delta(m)), w(p)(beta) (F, Delta(m)) for sequences of fuzzy numbers using generalized difference operator Delta(m) and a lacunary sequence theta and give some relations between them, where beta is an element of (0, 1] and p > 0. Furthermore, in the last section of paper, some inclusion theorems are presented related to the spaces S-0(beta)(F, Delta(m)) and w(p)(beta)(theta, f, F, Delta(m)) according to modulus function f.
Keywords: Fuzzy number; sequence of fuzzy numbers; statistical convergence; lacunary sequence; Cesaro summability; modulus function